Pengaruh Desentralisasi Fiskal Terhadap Pertumbuhan Ekonomi Kabupaten/Kota di Sulawesi Selatan Tahun 2016–2020 - Muh. Rifki Wahyudi; Wahyudin Wahyudin (Politeknik Statistika STIS, 2022)
Each development plan made by a region aims to achieve high economic growth. South Sulawesi, which is one of the provinces with the highest economic growth rate in Indonesia, during 2016 to 2020 its economic growth rate continued to slow down and was not evenly distributed. However, as a form of strengthening fiscal decentralization, regional funding sources in terms of PAD and balancing funds tend to increase. Therefore, this study aims to determine the effect of fiscal decentralization on the economic growth of districts/cities in South Sulawesi in 2016-2020 with the panel data regression analysis method. The data used are sourced from the publications of the BPS of South Sulawesi Province. The best model obtained is FEM with the FGLS-SUR estimation method. The results showed that the DBH ratio and the DAK ratio had a negative and significant effect, the DAU ratio had a positive and significant effect on the economic growth of districts/cities in South Sulawesi in 2016-2020. While the PAD ratio has no significant effect on the economic growth of districts/cities in South Sulawesi.